Effect of Curing Methods on the Mechanical Properties of Cement Mortar Contaminated with Heavy Crude Oil - Rajab Abousnina; Fahad Aljuaydi (Journal of Building Materials and Structures)
Crude oil contamination poses significant environmental issues, particularly in regions where oil spills affect soil and groundwater. Utilising damaged materials in construction offers a cost-effective rehabilitation strategy that repurposes waste and reduces pollution. This study examines the effects of curing methods and heavy crude oil contamination on the mechanical properties of cement mortar. Mortar samples with different amounts of heavy crude oil (0%, 2%, and 10%) were cured using air, water, and sealed plastic. Water curing attained the highest compressive strength across different pollution levels by maintaining moisture for complete hydration. In contrast, air curing resulted in the lowest strength, especially for uncontaminated and 2% oil samples, due to rapid drying that limited hydration and increased porosity. Curing techniques did not affect the strength of samples with 10% heavy crude oil, perhaps due to oil saturation impeding hydration. Increased oil contamination, particularly with heavy crude, significantly enhanced porosity and reduced compressive strength. The high viscosity and complex molecular structure of heavy crude oil form a dense coating around cement particles, hindering hydration and undermining the integrity of the cement matrix. The findings suggest that selecting an appropriate curing procedure for low-level crude oil may facilitate repurposing materials contaminated with heavy crude oil as sustainable, cost-effective alternatives for specific civil engineering applications, offering a viable option for oil-contaminated sand.